2018
DOI: 10.3389/fpsyg.2018.02616
|View full text |Cite
|
Sign up to set email alerts
|

Orff-Based Music Training Enhances Children’s Manual Dexterity and Bimanual Coordination

Abstract: How music training and expertise influence non-musical abilities is a widely researched topic. Most studies focus on the differences between adult professional musicians and non-musicians, or examine the effects of intensive instrumental training in childhood. However, the impact of music programs developed in regular school contexts for children from low-income communities is poorly explored. We conducted a longitudinal training study in such communities to examine if collective (Orff-based) music training en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 54 publications
0
17
0
3
Order By: Relevance
“…Good limb coordination is essential to achieve the desired movement outcome. Studies have shown that professional or experienced musicians, dancers and athletes outperform amateur or inexperienced groups in limb coordination (Martins, Neves, Rodrigues, Vasconcelos, & Castro, 2018;Mo & Chow, 2018;Seifert, Leblanc, Chollet, & Delignières, 2010;Seifert et al, 2011). Similarly, research has found that experienced musicians and dancers have better sensorimotor synchronisation ability than their less experienced counterparts (Jin et al, 2019;Karpati, Giacosa, Foster, Penhune, & Hyde, 2016;Repp, 2010;Sommer, Hager, Boraxbekk, & Ronnqvist, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Good limb coordination is essential to achieve the desired movement outcome. Studies have shown that professional or experienced musicians, dancers and athletes outperform amateur or inexperienced groups in limb coordination (Martins, Neves, Rodrigues, Vasconcelos, & Castro, 2018;Mo & Chow, 2018;Seifert, Leblanc, Chollet, & Delignières, 2010;Seifert et al, 2011). Similarly, research has found that experienced musicians and dancers have better sensorimotor synchronisation ability than their less experienced counterparts (Jin et al, 2019;Karpati, Giacosa, Foster, Penhune, & Hyde, 2016;Repp, 2010;Sommer, Hager, Boraxbekk, & Ronnqvist, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…For example, in a longitudinal training study (24-weeks), Orff-based music training was compared to a sports program and to no training. At post-test and 4-months, children in the music group outperformed control conditions on the Fine motor abilities assessed by the Purdue pegboard test (eye-hand coordination, motor speed, and bimanual coordination) [ 36 ]. Musicially-trained early adolescents (typical development) with more than six years of piano showed enhanced fine motor funciton and significangly better elbow and wrist proprioception abilities when compared to children with no musical experience [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…The non-dominant hand scores did not differ between both AME groups, compared to placebo. Previous studies have reported improvements in both hands after strength training in healthy elderly people [38] and music training in children [39], focusing more particularly on hand dexterity. Nevertheless, different outcomes for both hands have also been observed in studies determining motor function following sleep deprivation among medical personnel [40] and after an intravenous delta-9-tetrahydrocannabinol challenge [41].…”
Section: Discussionmentioning
confidence: 99%